2018
DOI: 10.1016/j.ijggc.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Fate of transition metals during passive carbonation of ultramafic mine tailings via air capture with potential for metal resource recovery

Abstract: This is a repository copy of Fate of transition metals during passive carbonation of ultramafic mine tailings via air capture with potential for metal resource recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 98 publications
0
33
0
Order By: Relevance
“…Dypingite and nesquehonite are common weathering products of ultramafic rocks (Wilson et al, 2006(Wilson et al, , 2014Power et al, 2007;Beinlich and Austrheim, 2012;Garcia del Real et al, 2016;Lin et al, 2017), and are documented CO 2 sinks that can be used to store CO 2 (Power et al, 2007(Power et al, , 2013a(Power et al, , b, c, 2016Pronost et al, 2011;Bea et al, 2012;499 Assima et al, 2012499 Assima et al, , 2014cHarrison et al, 2013aHarrison et al, , 2015Harrison et al, , 2016Harrison et al, , 2017Wilson et al, 2014;McCutcheon et al, 2014;Morgan et al, 2015;Hamilton et al, 2016Hamilton et al, , 2018Gras et al, 2017). 501…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dypingite and nesquehonite are common weathering products of ultramafic rocks (Wilson et al, 2006(Wilson et al, , 2014Power et al, 2007;Beinlich and Austrheim, 2012;Garcia del Real et al, 2016;Lin et al, 2017), and are documented CO 2 sinks that can be used to store CO 2 (Power et al, 2007(Power et al, , 2013a(Power et al, , b, c, 2016Pronost et al, 2011;Bea et al, 2012;499 Assima et al, 2012499 Assima et al, , 2014cHarrison et al, 2013aHarrison et al, , 2015Harrison et al, , 2016Harrison et al, , 2017Wilson et al, 2014;McCutcheon et al, 2014;Morgan et al, 2015;Hamilton et al, 2016Hamilton et al, , 2018Gras et al, 2017). 501…”
Section: Discussionmentioning
confidence: 99%
“…Ultramafic rock such as serpentinite contributes disproportionately to the release of chromium globally during natural weathering processes compared to other rock-types, owing to its high reactivity and high chromium content (McClain and Maher, 2016;Beinlich et al, 2018). It has recently been observed that secondary Mg-carbonate minerals formed during the weathering of ultramafic rock can help to mitigate the release of metals such as chromium, due both to incorporation of the metals into the carbonate minerals, and trapping of particulates within carbonate cement (Hamilton et al, 2016;Hamilton et al, 2018). The relative stability and mechanism of phase transformations is highly relevant to the cycling of potential contaminants like chromium in both natural and engineered ultramafic weathering environments.…”
Section: Discussionmentioning
confidence: 99%
“…It has been puzzling for early researchers why stichtite occurs in only a few chromite-rich serpentinites, if it is indeed only a surface weathering product. It is now reported that stichtite and other hydrotalcite minerals will form as a surface weathering product when ultramafic mine tailing pore water has pH 8.4 to 9.1 [38] and 8.8 to 9.4 [43]. It is also known that stichtite can form in active deep-sea submarine serpentinizing systems with pH 9 to 12.5 conditions [10,11,44,45].…”
Section: Structural and Geochemical Insightsmentioning
confidence: 99%
“…While it is possible that these compositional trends may reflect the abundance of reactants within the serpentinizing system, it is also possible that this compositional variation is a record of serpentinizing fluid pH. In host material with high porosity and permeability, such as ultramafic mine tailings, it has been demonstrated that stichtite can form as a weathering product, and exchange ions with the pore waters [42,43]. Future workers should explore the possibility of mapping spatially this potential fossil pH record for specific deposits, and examine the ion exchange capacity of this mineral, and specifically which sites may be prone to exchange, and which may bind ions more tightly.…”
Section: Structural and Geochemical Insightsmentioning
confidence: 99%
“…Other research groups at the University of Queensland and Monash University, Australia have been working on different aspects of mineral carbonation, field studies and the use of waste materials [103][104][105][106][107][108][109][110]. Recent research investigated ultramafic mine tailings as feedstock because they contain abundant Mg-rich silicate and hydroxide minerals and have a smaller grain size and increased reactive surface area due to ore processing [106,107]. Table 2 presents a summary of research on mineral carbonation in Australia.…”
Section: Mineral Carbonation In Australiamentioning
confidence: 99%